Occupational Stress as Mediator of Relationship between Workload, Emotional Intelligence and Teacher’s Performance in Probolinggo Regency - Ngatimun Ngatimun; Titik Musriati; Judi Suharsono; Sulis Dyah Candra (Politeknik Ganesha Medan, 2020)
This research investigates occupational stress as mediator of relationship between workload, emotional intelligence and performance of teachers in Probolinggo regency. A number of 198 teachers from both public and private secondary school in the regency were randomly selected. Data collected using questionnaires and analyzed using Structural Equation Modelling (SEM). The analysis on the validity of workload, emotional intelligence, occupational stress and performance instrument gives result above 0.139 (rtable). This tells that all instruments are valid while the reliabilities based on the analysis result in Alpha coefficient of 0.6, which is reliable. The results showed that both workload and emotional intelligence significantly influence work stress and teacher performance, and work stress is able to mediate the effect of workload and emotional intelligence on teacher performance.